2019
DOI: 10.2147/ndt.s198804
|View full text |Cite
|
Sign up to set email alerts
|

<p>Borderline personality disorder, trauma, and the hypothalamus–pituitary–adrenal axis</p>

Abstract: Borderline personality disorder (BPD) is a complex psychiatric illness for which treatment poses a significant challenge due to limited effective pharmacologic treatments, and under-resourced psychological interventions. BPD is one of the most stigmatized conditions in psychiatry today, but can be understood as a modifiable, neurodevelopmental disorder that arises from maladaptive responses to trauma and stress. Stress susceptibility and reactivity in BPD is thought to mediate both the development and maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…Coccaro et al reported direct correlations between cerebrospinal fluid (CSF) glutamate levels and composite measures of aggression, impulsivity, and impulsive aggression in healthy subjects and patients with personality disorders [ 16 ]. Glutamate-mediated neuroinflammation and HPA axis dysregulation are seen with BPD, early life trauma, and impulsivity [ 17 , 10 ]. Esketamine’s potential action on patients with BPD can be partially explained by its very well-documented effect on the glutamate receptor antagonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coccaro et al reported direct correlations between cerebrospinal fluid (CSF) glutamate levels and composite measures of aggression, impulsivity, and impulsive aggression in healthy subjects and patients with personality disorders [ 16 ]. Glutamate-mediated neuroinflammation and HPA axis dysregulation are seen with BPD, early life trauma, and impulsivity [ 17 , 10 ]. Esketamine’s potential action on patients with BPD can be partially explained by its very well-documented effect on the glutamate receptor antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…Both physical and psychological pain converge into the opioid system, and low levels of endogenous opioids in BPD lead to chronic dysphoria, lack of sense of well-being, and a chronic feeling of emptiness. Self-harm attempts have been shown to increase opioid levels in patients with BPD [ 17 ]. Ketamine recalibrates and improves basal opioid levels, which can hypothetically improve symptoms of BPD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is overlap in the neurochemistry and neurostructural changes observed in PTSD, BPD and cPTSD, with no clear differentiation between the three conditions in regards to HPA axis function or subsequent alterations ( 29 ). For instance, HPA axis overactivity has been implicated in BPD ( 60 ) and PTSD ( 56 ), and this dysfunction in both disorders is believed to closely mirror each other ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis represents a key stress response system, and growing evidence suggests that it is dysfunctional in the BPD population. 6 Further, sleep, and in particular deep sleep, has an inhibitory influence on the HPA axis, whereas activation of the HPA can lead to sleeplessness. 7…”
Section: Methodsmentioning
confidence: 99%